(untitled) (Rajarshi Janak University Research Journal, 2024)
One of the generalizations of Metric space is a Menger space which was introduced in 1942 by Menger who used distribution functions also called probabilistic distance instead of non-negative real numbers as values of the metric. In this paper, we obtain a unique common fixed point for four pairwise weakly compatible self-mappings which use the conditions of E.A. property and also satisfy certain sufficient conditions in setting of Menger space.